EVALUATION OF SOLIDS CARRYING CAPACITY IN AERATED FLUID DRILLING: REAL SCALE TESTS AND MODELING - Martins, A. L.; Lourenço, A. M. F.; Andrade Jr., P. H.; Silva Jr., V.; Silva, P. R. C.; Nakagawa, E. Y. (Revista de Engenharia Térmica, 2003)
This paper summarizes the results of two sets of experimental tests performed at PETROBRAS real scale test facility aiming the evaluation of solids return times in aerated fluid drilling. The effect of the following parameters was studied: liquid and gas injection rates, particle diameter and depth. Results indicate that the gas has a major effect in accelerating the liquid phase, which would be responsible for carrying the particles to the surface. The concept of effective liquid velocity coupled with an adequate procedure for particle sedimentation velocity calculation reproduced the experimental results adequately.